(untitled) (Theatrum historiae, 2013)
The article is focused on two main representatives of the Czechoslovak political exile in Ethiopia after 1948. Bedřich Hildprandt, belonging to aristocratic family Hildprandt of Ottenhausen, served as an administrator of the imperial stud farm in Addis Ababa, while Ferdinand Veverka became a diplomatic counselor at the imperial court in Addis Ababa, where he was largely using his previous vast experience from the Czechoslovak diplomatic services. Description of Hildprandt ́s and Veverka ́s lives is very close to the contributions that analyse a declining position of social elites in Czechoslovakia after 1918, as well as to those inquiries focused on Czechoslovak emigration in Sub-Saharan Africa. The basic aim of this article is to introduce the above-mentioned personalities and to describe difficulties that preceded their decisions to leave definitely Czechoslovakia.